2005
DOI: 10.4103/0378-6323.13996
|View full text |Cite
|
Sign up to set email alerts
|

Epidermolysis bullosa pruriginosa - Report of three cases

Abstract: Epidermolysis bullosa pruriginosa, a genetic mechanobullous disease, is characterized by pruritus, lichenified or nodular prurigo-like lesions, occasional trauma-induced blistering, excoriations, milia, nail dystrophy and albopapuloid lesions, appearing at birth or later. Scarring and prurigo are most prominent on the shins. Treatment is unsatisfactory. We report three such cases: two of them first cousins, are described with history of blisters since childhood, followed by intensely pruritic lesions predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 3 publications
0
17
0
2
Order By: Relevance
“…These include topical treatments (eg, tacrolimus), 14 systemic agents (eg, ciclosporin 17 or thalidomide 13 ), and cryotherapy. 12 In summary, we have investigated a family with EBP in whom we have identified a COL7A1 mutation in affected individuals as well as two clinically unaffected family members who may be at risk from developing EBP in the future. Gene sequencing predicts an EBP phenotype, but currently neither individual has any cutaneous abnormalities or pruritus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These include topical treatments (eg, tacrolimus), 14 systemic agents (eg, ciclosporin 17 or thalidomide 13 ), and cryotherapy. 12 In summary, we have investigated a family with EBP in whom we have identified a COL7A1 mutation in affected individuals as well as two clinically unaffected family members who may be at risk from developing EBP in the future. Gene sequencing predicts an EBP phenotype, but currently neither individual has any cutaneous abnormalities or pruritus.…”
Section: Discussionmentioning
confidence: 97%
“…Since the initial publication, a number of other cases of EBP have been reported, collectively highlighting the distinctive nature and clinical spectrum of this form of DEB. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Inheritance of EBP may be dominant or recessive, but the cause of the pruritus is uncertain-it is not caused by a specific type of COL7A1 mutation. Other factors, such as atopy or iron deficiency, have been implicated, but no universal abnormality has been found to link all cases of EBP.…”
mentioning
confidence: 99%
“…[8] Trials of a few interventions which have been found to have a variable response in EBP are topical tacrolimus, [4] systemic ciclosporin, [9] Dapsone, [10] thalidomide, [7] and cryotherapy. [5] …”
Section: Discussionmentioning
confidence: 97%
“…Lesions may develop at birth. [5] to as late as 40 years of age. [3] Differential diagnoses that need to be ruled out before one can conclusively narrow down to this diagnosis are lichen simplex chronicus, hypertrophic lichen planus, lichen amyloidosis, prurigo nodularis, dermatitis artifacta among others.…”
Section: Discussionmentioning
confidence: 98%
“…Es gibt zahlreiche Differentialdiagnosen wie Lichen planus hypertrophicus, Lichen simplex chronicus, Prurigo nodularis, kutane Amyloidose, Nekam's disease (Lichen ruber monileformis) und Dermatitis artefacta [4,5], doch keine davon würde bei histopathologischer Untersuchung subepidermale Spalten aufweisen [4,10]. Andere Differentialdiagnosen sind bullöse Autoimmunerkrankungen, wie die Epidermolysis bullosa acquisita und das lokalisierte bullöse Pemphigoid.…”
unclassified